Perilaku Bullying Terhadap Interaksi Sosial Pada Remaja Di SMP Negeri 1 Meulaboh - samsidar samsidar; Nurromsyah Nasution; Fitri Apriani; Orita Satria (BALE LITERASI, 2025)
Background: Bullying behavior is an action that is carried out repeatedly from time to time by one or more people and the behavior violates norms because it is negative, in this case bullying behavior consists of several namely physical, verbal, relational, sexual, cyber bullying, One of the impacts that occurs due to bullying is social interaction.Objective: To relate the tendency of bullying behavior to social interaction in adolescents in SMP 1 Meulaboh. Methods: This study is a quantitative research, a type of analytical survey research with a cross sectional approach. The sample consisted of 100 respondents who were selected by the Statified random sampling technique. Data collection was carried out from January 10 to 14, 2024, and analyzed using the Chi-Square statistical test. Result: The results of the analysis showed the relationship between the tendency of bullying behavior g to social interaction in adolescents at SMP 1 Meulaboh, West Aceh Regency with a p value of 0.044< 0.05. Conclusion: Bullying behavior has a significant effect on social interaction in adolescents. Suggestion: It is recommended that the school can facilitate a meeting of students' parents to provide education about the causes and impacts of bullying behavior in adolescents.